2016
DOI: 10.15253/2175-6783.2015000100003
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation: experience of men in hemodialysis entered on the waiting list

Abstract: Objective: to know the experiences of men with chronic renal failure under hemodialysis treatment entered on the kidneytransplant waiting list. Method: qualitative study based on the principles of the National Policy for Integral Attention toMen’s Health and Masculinity, conducted with 11 participants in a hemodialysis service, through serial semi-structuredinterviews and inductive data analysis. Results: the following categories emerged: Gaps between the health policies and thereality of the male population a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…On the one hand, they envision the possibility of a new life, but over the years they experience feelings of frustration, hopelessness and disappointment due to the delay in receiving the organ. 17 The delay is faced as a reality imposed due to the large number of enrollees compared to the small amount of organs captured. 18 It is necessary that the health team, in particular, the nurse, due to the attributions of care inherent in their profession, establish a relationship of trust providing clarifications regarding the surgical treatment involving all its aspects, from the benefits, to the existing risks .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the one hand, they envision the possibility of a new life, but over the years they experience feelings of frustration, hopelessness and disappointment due to the delay in receiving the organ. 17 The delay is faced as a reality imposed due to the large number of enrollees compared to the small amount of organs captured. 18 It is necessary that the health team, in particular, the nurse, due to the attributions of care inherent in their profession, establish a relationship of trust providing clarifications regarding the surgical treatment involving all its aspects, from the benefits, to the existing risks .…”
Section: Resultsmentioning
confidence: 99%
“…19 It has been demonstrated in some studies with renal patients that they adapt and acquire safety in the dialysis treatment justifying their questions and choices in performing the transplant. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Other studies have shown that patients see hemodialysis as something safe, which brings life, while transplantation is related to doubts and uncertainties. [8][9][10][11][12][13][14][15][16][17][18][19][20] In a recent study, reports of transplant patients on the significant changes after transplantation, such as regaining autonomy, without the numerous restrictions caused by hemodialysis, and the possibility of performing activities that were previously not possible, have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In everyday, being-there appears impersonal to care, not to assume because do not decide about their health, being released on a day-by-day dialysis and waiting for a transplant. Thus, they have no control or knowledge about their ranking on the waiting list; and perform only the procedures, tests, protocols and certificates about their aptitude to belong to the waiting list for a possible kidney transplant (18) . Thus, heed the health team's decision and not from their needs and complaints.…”
Section: Discussionmentioning
confidence: 99%